2022
DOI: 10.3389/fmed.2022.968814
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and sarcopenia: Current knowledge domain and emerging trends

Abstract: ObjectiveNon-pharmacological management like nutrient supplements has shown positive impacts on muscle mass and strength, which has burgeoned clinical and research interest internationally. The aim of this study was to analyze the current knowledge domain and emerging trends of nutrition-related research in sarcopenia and provide implications for future research and strategies to prevent or manage sarcopenia in the context of aging societies.Materials and methodsNutrition- and sarcopenia-related research were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The United States administration has adequate resources with strong collaboration and partnerships, making it the worldwide leader in food and nutritional research [ 32 , 65 , 66 ]. This article found that the USA is the most productive country regarding malnutrition and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The United States administration has adequate resources with strong collaboration and partnerships, making it the worldwide leader in food and nutritional research [ 32 , 65 , 66 ]. This article found that the USA is the most productive country regarding malnutrition and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there are still no research and articles with bibliometric analysis on the biomarkers for PFS, and only a few bibliometric studies in certain aspects of sarcopenia (such as sarcopenia and nutrition, sarcopenia and surgery, physical activity and sarcopenia) have been published (16)(17)(18)(19)(20). Therefore, the aim of this study was to identify the current study hotspots, status, and trends in the area of biomarkers and molecular mechanisms for PFS (based on bibliometric analysis and visualization technology).…”
Section: Methodsmentioning
confidence: 99%
“…As there are currently no approved drugs for sarcopenia [6 ▪ ], a healthy lifestyle comprising a high-quality diet and resistance exercise have been championed as the most effective strategy for sarcopenia prevention and treatment [7,8 ▪▪ ,9 ▪▪ ,10 ▪ ]. The nutrition-sarcopenia research field has grown substantially since the implementation of the sarcopenia concept 30 years ago [11], and several nutrition approaches have been adopted to test their effectiveness in mitigating sarcopenia; from a single nutrient to a whole food and a whole diet approach [9 ▪▪ ,12 ▪ ]. Although two recent consensus guidelines for sarcopenia diagnosis, prevention, and management [8 ▪▪ ,13 ▪▪ ], have endorsed nutritional assessment and the promotion of balanced diets with sufficient high-quality nutrients, such as protein for the prevention of sarcopenia, these recommendations were mostly supported by observational epidemiological findings.…”
Section: Introductionmentioning
confidence: 99%